2010
DOI: 10.1016/j.devcel.2010.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Light- and Brassinosteroid-Signaling Pathways by a GATA Transcription Factor in Arabidopsis

Abstract: SUMMARY Light and brassinosteroid (BR) antagonistically regulate the developmental switch from etiolation in the dark to photomorphogenesis in the light in plants. Here we identify GATA2 as a key transcriptional regulator that mediates the crosstalk between BR- and light-signaling pathways. Overexpression of GATA2 causes constitutive photomorphogenesis in the dark, whereas suppression of GATA2 reduces photomorphogenesis caused by light, BR deficiency, or the constitutive photomorphogenesis mutant cop1. Genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
242
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(250 citation statements)
references
References 53 publications
6
242
0
2
Order By: Relevance
“…BR promotes rice leaf bending by increasing the expansion of adaxial cells of the laminar joint, through BZR1 regulation of a pair of helix loop helix/basic helix loop helix (HLH/bHLH) factors (42). Such independent mechanisms for a common function support an adaptive value for BR regulation of plant architecture, perhaps to optimally position photosynthetic organs according to environmental or endogenous conditions in addition to coregulation of other photosynthetic aspects such as expression of photosynthetic genes and stomata formation (31,(43)(44)(45). Detailed analyses of the architecture of BR mutants in other species will advance our understanding of the evolution of BR's role in plant architecture.…”
Section: Discussionmentioning
confidence: 99%
“…BR promotes rice leaf bending by increasing the expansion of adaxial cells of the laminar joint, through BZR1 regulation of a pair of helix loop helix/basic helix loop helix (HLH/bHLH) factors (42). Such independent mechanisms for a common function support an adaptive value for BR regulation of plant architecture, perhaps to optimally position photosynthetic organs according to environmental or endogenous conditions in addition to coregulation of other photosynthetic aspects such as expression of photosynthetic genes and stomata formation (31,(43)(44)(45). Detailed analyses of the architecture of BR mutants in other species will advance our understanding of the evolution of BR's role in plant architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have detailed the mechanisms involved in hypocotyl cell elongation regulated by light, phytohormones, and transcription factors (Wang et al, 2002;Niwa et al, 2009;Luo et al, 2010;Fan et al, 2012). In addition, a recent study showed that pectin-dependent cell wall homeostasis is important for BR regulation of hypocotyl growth (Wolf et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This regulation is especially relevant late in the night, when PIF4 transcription is upregulated and the protein is stable. Although BES1 and BZR1 were reported to not be significantly affected by light (Luo et al 2010), the active nonphosphorylated forms of the PIF4 and BES1/BZR1 factors overlap only during late night, BES1/BZR1 coactivator function thus having a relevant role in timing PIF4 transcriptional activity and in rhythmic hypocotyl growth. These results confirm a main function of the PIFs and BES1/BZR1 factors in cell elongation and highlight a role of these two families of bHLH factors as main integrators of light, BR, and GA signals by means of PHYB-and BIN2-induced destabilization and inactive complex formation with the DELLAs.…”
mentioning
confidence: 99%